1994
DOI: 10.1111/j.1540-4560.1994.tb01203.x
|View full text |Cite
|
Sign up to set email alerts
|

Dual‐Processing in Value Self‐Confrontation: The Role of Need for Cognition

Abstract: Rokeach (1973) developed the method of value self-confrontation (VSC) in an attempt to change people's behavior by changing the value hierarchy underlying that behavior. The present research examined the role of need for cognition, defined by Cacioppo, Petty, and Kao (1984) as an individual's tendency to engage in and enjoy effortjiul cognitive endeavors, in the VSC process. Two studies demonstrated that the VSC procedure was equally effective for collegeage participants, regardless of their level of need for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

1997
1997
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 12 publications
0
4
0
Order By: Relevance
“…''Need for cognition refers to an individual's tendency to engage in and enjoy effortful cognitive endeavors" (Cacioppo et al, 1984,). While individuals high and low in need for cognition may use different ''routes" of information processing to translate values into attitudes and behaviors, research has shown that the values themselves are not related to their need for cognition (Waller, 1994). That is, individuals with a high need for cognition can have the same values as those scoring low on the need for cognition scale.…”
Section: Scales To Test Convergent and Discriminant Validitymentioning
confidence: 99%
“…''Need for cognition refers to an individual's tendency to engage in and enjoy effortful cognitive endeavors" (Cacioppo et al, 1984,). While individuals high and low in need for cognition may use different ''routes" of information processing to translate values into attitudes and behaviors, research has shown that the values themselves are not related to their need for cognition (Waller, 1994). That is, individuals with a high need for cognition can have the same values as those scoring low on the need for cognition scale.…”
Section: Scales To Test Convergent and Discriminant Validitymentioning
confidence: 99%
“…Although much work has been done to determine whether or not and to what extent values are structured as a dynamic system (e.g., Schwartz & Bilsky, 1987), only a few published empirical studies have directly tested if and to what extent values function in the fashion of a dynamic system (Rokeach, 1973;Waller, 1994). These studies employed an experimental design and samples of college students to support the system-based proposition that a discrepancy between a preferred state (in this case values) and an actual state (other values or behaviors) prompts a change in either the preferred and/or actual state to decrease the discrepancy.…”
Section: A Propositional Model Of Work Values Developmentmentioning
confidence: 99%
“…The VSC has also been used in prevention research for tobacco cessation and weight control (Conroy, 1979;Schwartz & Inbar-Saban, 1988). The potential theories and cognitive processes of behavior change associated with VSC, such as the Belief System Theory and the Dual Processing Cognitive mechanism have also been examined (Grube et al, 1994;Waller, 1994). However, the long-term effect of the VSC method on tobacco cessation is unknown and this method has not been adapted by current tobacco control practitioners.…”
Section: Implications and Recommendationsmentioning
confidence: 99%